PENYULUHAN HUKUM SEBAGAI TINDAKAN PREVENTIF KENAKALAN REMAJA DI MA RAUDHATUL MUTA'ALIMIN, KABUPATEN BANDUNG - Sari, Dela Permata; Sukma Cipta, Eliva; Ruslan, Denni; Yusyahadah, Fahmy Wahyuni; Hasan, Jaenal; Fitriyani, Hani; Nurhayati, Ai; Rahman, Fauzi (LPPM Universitas Bina Bangsa, 2024)
Juvenile delinquency is one of the social problems that can have an impact on the development of children's character and future. Legal counseling on juvenile delinquency is important to provide an understanding of the legal and social impact of this deviant behavior. This counseling aims to increase students' awareness of juvenile delinquency and its legal consequences. The methods used in this counseling are interactive lectures, group discussions, and symbolic activities in the form of fingerprints on white cloth as a commitment to stay away from negative behavior. The results showed an increase in students' understanding of juvenile delinquency and a real commitment from students to avoid deviant behavior